2014
DOI: 10.1016/j.breast.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breast cancer treatments on sleep disturbances – A systematic review

Abstract: a b s t r a c tSleep disturbances are highly prevalent in women with breast cancer; side effects of cancer treatment may worsen pre-existing sleep problems and have been pointed to as important determinants of their incidence. Therefore, we aimed to assess the association between different types of breast cancer treatment and sleep disturbances, through a systematic review. Medline (using PubMed), CINAHL Plus with full text, PsycINFO and Cochrane Central Register of Controlled Trials (Central) were searched fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 64 publications
3
62
0
3
Order By: Relevance
“…Regarding clinical characteristics we found that head and neck, Gastrointestinal, and urologic cancer were the types of cancer most associated with insomnia. The strongest associated factors were lowest SES (OR= 3.849 (1,684-5,159)), Head and neck cancer (OR=3.129 (1,985-5,129)), urologic cancer (OR= 2.919 (1,985-5,295)), Surgery (OR= 3.201 (1,157)), and Chemotherapy (OR= 3.154 (2,818)). …”
Section: Results Of Insomniamentioning
confidence: 99%
“…Regarding clinical characteristics we found that head and neck, Gastrointestinal, and urologic cancer were the types of cancer most associated with insomnia. The strongest associated factors were lowest SES (OR= 3.849 (1,684-5,159)), Head and neck cancer (OR=3.129 (1,985-5,129)), urologic cancer (OR= 2.919 (1,985-5,295)), Surgery (OR= 3.201 (1,157)), and Chemotherapy (OR= 3.154 (2,818)). …”
Section: Results Of Insomniamentioning
confidence: 99%
“…Hasil studi lain yang menggambarkan penyebab yang memengaruhi kualitas tidur pasien kanker payudara antara lain: (1) rasa sakit akibat prosedur pembedahan (Rute et al, 2014). (2) rasa terbakat akibat radioterapi yang terjadi pada 85% dari 73 pasien yang diteliti menyebabkan mereka harus terbangun sebanyak 15 kali (Dhruva et al, 2012).…”
Section: Pendahuluanunclassified
“…Efek yang sering terlihat setelah operasi mastektomi berupa mual dan muntah, nyeri persisten pasca operasi, stres dan gangguan emosional (Black and Hawks, 2014). Prosedur pembedahan mastektomi yang dilakukan juga dapat menghasilkan rasa nyeri dan respon inflamasi yang dapat memengaruhi kualitas tidur (Rute et al, 2014).…”
Section: Pembahasan Gambaran Kualitas Tidur Berdasarkan Terapi Yang Dunclassified
“…Although a high proportion of breast cancer patients may present sleep disturbances before beginning treatment [8,9], cancer treatment has been associated with the occurrence of sleep disturbances among women with breast cancer [10,11]. In a recent systematic review, women submitted to chemotherapy (CTX), as well as radiotherapy, tended to report higher levels of sleep disturbances; inconsistent findings were observed regarding the different options for surgery and the use of hormonal treatment [12]. The only prospective study included in this review evaluated patients before surgery and followed them for 6 months, concluding that adjuvant CTX was associated with gradual increases in sleep disturbances that peaked at the third month and then decreased until 6 months after surgery [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have addressed the relation between breast cancer treatments and sleep disturbances, the achievement of more robust findings was hampered by limitations such as the absence of control for confounding, the use of non-standardized measures to evaluate sleep quality and the scarcity of longitudinal analyses taking into account sleep quality of the patients at baseline, in addition to some lack of detail in the description of all treatments [12]. Data from prospective studies with an evaluation of participants prior to treatments and providing a detailed assessment of the effect of breast cancer treatments may contribute to a more accurate characterization of sleep quality determinants.…”
Section: Introductionmentioning
confidence: 99%